2020
DOI: 10.12688/wellcomeopenres.15730.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D deficiency on neurobehavioural outcomes in children: a systematic review

Abstract: Introduction: Vitamin D plays an important role in brain development in experimental studies; however, the effect of vitamin D deficiency on child development remains inadequately characterized. We aimed to estimate the effects of vitamin D deficiency on neurobehavioural outcomes in children up to 18 years of age. Methods: We searched PubMed, EMBASE, PsycINFO, Scopus, Cochrane Library, Web of Science and Open Grey for published studies up to 10th January 2020. We included all studies that assessed the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 74 publications
0
27
0
2
Order By: Relevance
“…Во всем мире существует проблема низкой информированности родителей о роли витамина D в организме, источниках его поступления, последствиях дефицита и организации профилактического приема препаратов витамина D. При этом лишь каждый 4-й ребенок в возрасте до 2 лет получает профилактическую дозу холекальциферола [17]. Большинство взрослых также не осведомлены и не принимают витамин D [18][19][20][21].…”
Section: таблица 5 уровень 25(он)d3 в плазме крови у детей в зависимости от сезона года и длительности инсоляции Table 5 Level 25(oh)d3 Dunclassified
See 1 more Smart Citation
“…Во всем мире существует проблема низкой информированности родителей о роли витамина D в организме, источниках его поступления, последствиях дефицита и организации профилактического приема препаратов витамина D. При этом лишь каждый 4-й ребенок в возрасте до 2 лет получает профилактическую дозу холекальциферола [17]. Большинство взрослых также не осведомлены и не принимают витамин D [18][19][20][21].…”
Section: таблица 5 уровень 25(он)d3 в плазме крови у детей в зависимости от сезона года и длительности инсоляции Table 5 Level 25(oh)d3 Dunclassified
“…В отношении подростков и детей старшего возраста нужно отметить, что частота тяжелого и умеренного дефицита 25(ОН)D 3 у них максимальная. Данные нарушения совпадают со временем ростового «скачка» и мощных гормональных изменений в организме ребенка, что может иметь различные негативные последствия, например увеличение риска реализации метаболического синдрома, сахарного диабета, увеличение риска канцерогенеза во взрослом возрасте и ряда других патологических состояний [1][2][3][4][5]19].…”
Section: таблица 5 уровень 25(он)d3 в плазме крови у детей в зависимости от сезона года и длительности инсоляции Table 5 Level 25(oh)d3 Dunclassified
“… 14 , 15 Associations between vitamin D concentrations and cognitive and motor functioning have not been systematically found. 16 However, previous evidence is based on observational studies, precluding causal inferences. Randomized clinical trials (RCTs), 17 , 18 , 19 , 20 as well as nonrandomized trials, 21 , 22 , 23 , 24 on vitamin D supplementation for children have been small, have typically focused on symptom severity among children with autism spectrum disorder or attention-deficit/hyperactivity disorder, and have reported mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found evidence for associations between maternal prenatal vitamin D status and child neurobehavioral outcomes to be mixed. [6] Some, but not all [7,8] previous studies have reported that low maternal vitamin D concentrations during pregnancy are associated with an increased risk of mental health problems in the offspring, including behavioral problems and diagnosis of attention deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and depression. [9][10][11][12][13][14][15] Lower cord blood 25(OH)D concentrations at birth have also been associated with poorer mental health outcomes [13,[16][17][18], however, these may be less predictive of child neurobehavioral outcomes, compared to early-and mid-pregnancy maternal measurements [6,11].…”
Section: Introductionmentioning
confidence: 99%